2007
DOI: 10.1152/japplphysiol.00185.2007
|View full text |Cite
|
Sign up to set email alerts
|

AMP deaminase deficiency is associated with lower sprint cycling performance in healthy subjects

Abstract: AMP deaminase (AMPD) deficiency is an inherited disorder of skeletal muscle found in approximately 2% of the Caucasian population. Although most AMPD-deficient individuals are asymptomatic, a small subset has exercise-related cramping and pain without any other identifiable neuromuscular complications. This heterogeneity has raised doubts about the physiological significance of AMPD in skeletal muscle, despite evidence for disrupted adenine nucleotide catabolism during exercise in deficient individuals. Previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 35 publications
3
58
0
3
Order By: Relevance
“…A null TT genotype and low T unaffected by AMPD1 genotypes [13]. In contrast, a faster power decrease and a lower mean power was demonstrated in individuals with TT and CT genotypes during the 30 s cycling test [27]. However, despite the 10% decline in the mean power, a better circulatory adaptation to exercise was found in TT and CT individuals with diminished muscular AMPD enzyme activity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A null TT genotype and low T unaffected by AMPD1 genotypes [13]. In contrast, a faster power decrease and a lower mean power was demonstrated in individuals with TT and CT genotypes during the 30 s cycling test [27]. However, despite the 10% decline in the mean power, a better circulatory adaptation to exercise was found in TT and CT individuals with diminished muscular AMPD enzyme activity.…”
Section: Discussionmentioning
confidence: 91%
“…The AMPD1 polymorphism is a nonsense (C34T) mutation in exon 2 resulting in AMPD enzyme deficiency [27,28]. The AMPD1 gene is presented in three genotypes (CC, TC and TT).…”
Section: Introductionmentioning
confidence: 99%
“…This Wnding lends little support to the proposed causal relationship between mAMPD deWciency and myopathic symptoms. Nevertheless, several recent studies have shown diminished exercise performance in asymptomatic individuals with an inherited mAMPD deWciency (De Ruiter et al 2002;Fischer et al 2007;Rico-Sanz et al 2003), which does indicate a physiological role for this enzyme in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…In the overwhelming majority of cases, mAMPD deWciency is due to a 34C>T transition in exon 2 of the AMPD1 gene, which creates a nonsense codon (Q12X) that prematurely terminates translation (Morisaki et al 1992). A less prevalent AMPD1 nonsense mutation, characterized by a single nucleotide deletion in exon 5 (404delT), also results in a total loss of mAMPD activity (Fischer et al 2007). Homozygotes for the 34C>T mutation and compound heterozygotes carrying the 34C>T and the 404delT mutations in diVerent AMPD1 alleles (collectively termed MM) have extremely low skeletal muscle AMPD activities, individuals with one normal and one mutant allele (NM) have intermediate activities, and those with two AMPD1 normal alleles (NN) have high activities (Fischer et al 2007;Norman et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…AMPD1 is preferentially expressed at high levels in type II skeletal muscle, where it influences the levels of inorganic phosphate, AMP, ADP, and phosphocreatine (Coley et al, 2012). Patients with an inherited defect in AMPD1 expression often have significantly decreased muscle performance, suggesting that the purine nucleotide catabolic pathway plays a role in short-term energy production (Fischer et al, 2007;Norman et al, 2008). The AMPD1 gene is highly expressed in skeletal muscle, and is involved in the rate-limiting step of the purine nucleotide cycle, allowing repletion of ATP stores.…”
Section: Introductionmentioning
confidence: 99%